2020
DOI: 10.3390/cancers12061527
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Alterations of Depressed Colorectal Neoplasm Predict the Survival and Response to Oxaliplatin in Proximal Colon Cancer

Abstract: Depressed colorectal neoplasm exhibits high malignant potential and shows rapid invasiveness. We investigated the genomic profile of depressed neoplasms and clarified the survival outcome and treatment response of the cancers arising from them. We examined 20 depressed and 13 polypoid neoplasms by genome-wide copy number analysis. Subsequently, we validated the identified copy number alterations (CNAs) in an independent cohort of 37 depressed and 42 polypoid neoplasms. Finally, the CNAs were tested as biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The experience of endoscopists and surgeons is among these factors and could be a possible confounder for recurrence. However, all T1 cancers were treated using the same protocol at our center, thus mitigating such bias [34]. In view of the retrospective design of this study, measured factors such as tumor size, anatomic location, and macroscopic shape may not have been standardized.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of endoscopists and surgeons is among these factors and could be a possible confounder for recurrence. However, all T1 cancers were treated using the same protocol at our center, thus mitigating such bias [34]. In view of the retrospective design of this study, measured factors such as tumor size, anatomic location, and macroscopic shape may not have been standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al used the machine learning method of supervised learning to study and analyze the survival data of colon cancer patients and proposed the expression characteristics of colon cancer genes [ 1 ]. Chang et al conducted research on depressive and polypoid colon cancer tumors and found that depressive colon cancer tumors showed rapid invasive characteristics during patient survival [ 2 ]. Li et al proposed a postoperative survival assessment method for colon cancer patients by analyzing the blood test results of colorectal cancer, combined with data classification and machine learning methods [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher TMB suggests a likelihood of a better response to immunotherapy [52]. Furthermore, it has previously been demonstrated that tumors with microsatellite instabilityare associated with a higher TMB, which would be more susceptible to the treatment of immunotherapy [35,53,54]. Therefore, further investigations on the relationship between TMB, PD1/PD-L1 expression, and P-CA score were performed.…”
Section: Discussionmentioning
confidence: 99%